Analysis on technological features of pile foundations construction in frozen and seasonal thawing soils - Montayeva, А. A.; Zhussupbekov, A.; Kaliakin, V. N.; Montayev, S. (My University, 2021)
This article assesses the more productive methods for thawing seasonally frozen soils. The most rational and progressive method of thawing ,seasonally frozen soils involves putting antifreeze additives into the soil. New goals and objectives for the development of pile foundation construction technology in seasonally frozen soils in northern and central regions of Kazakhstan is presented.В данной статье дается оценка наиболее продуктивным методам оттаивания сезонно мерзлых почв. Самый рациональный и прогрессивный способ оттаивания сезонно мерзлых грунтов - внесение в грунт антифризов. Представлены новые цели и задачи по развитию технологии строительства свайных фундаментов в сезонно мерзлых грунтах северных и центральных регионов Казахстана.
IOP Conference Series: Earth and Environmental Science: 14th Baltic Sea Region Geotechnical Conference (18-19 January 2021).
Keywords: импакт-фактор 2021; дальнее зарубежье; зарубежное издание; конференции; зарубежные авторы; мерзлый грунт; почва; свайные фундаменты; скопус